Parasitological and biochemical studies on cutaneous leishmaniasis in Shara'b District, Taiz, Yemen - Qhtan Asmaa; Salwa AL-Shamerii; Mohammed Al-Tag; Adam AL-Shamerii; Yiping Li; Bashir H. Osman (BMC, 2017)
Abstract Background The leishmaniasis is a group of diseases caused by intracellular haemoflagellate protozoan parasites of the genus Leishmania. Leishmaniasis has diverse clinical manifestations; cutaneous leishmaniasis (CL) is the most common form of leishmaniasis which is responsible for 60% of disability-adjusted life years. CL is endemic in Yemen. In Shara'b there is no reference study available to identify the prevalence of endemic diseases and no investigation has been conducted for diagnosing the diseases. Methods This study was conducted in villages for CL which collected randomly. The study aimed at investigating the epidemiological factors of CL in Shara'b by using questioner. Symptoms of lesions in patients suffering from CL, confirmed by laboratory tests, gave a new evidence of biochemical diagnosis in 525 villagers aged between 1 and 60 years old. Venous bloods were collected from 99 patients as well as from 51 control after an overnight fast. Results The percentage prevalence of CL was found 18.8%. The prevalence rate of infection among males (19.3%) was higher than females (18.40%). Younger age group (1-15) had a higher prevalence rate (20.3%) than the other age groups. Furthermore, the population with no formal education had the higher rate of infection (61% of the total). A significant increase of serum malondialdehyde (P < 0.001) in CL patients was obtained. The highest level of MDA may be due to over production of ROS and RNS results in oxidative stress and the acceleration of lipid peroxidation in CL patients. Conclusions There were high prevalence rates of CL in Shara'b. The patient who had CL has been found with many changes in some biochemical levels. This study provides a clear indication on the role of MDA as an early biochemical marker of peroxidation damage occurring during CL. Increased uric acid, and catalase activity was provided of free radical.